13. Quality of Broiler Meat after Treatment of Jaloh Extract and Turmeric Extract and Infected By Eimeria tenella - M. Chairul Amri; Sugito Sugito; Sulasmi Sulasmi; Nurliana Nurliana; Ismail Ismail; Mahdi Abrar (Universitas Syiah Kuala, 2018)
The aim of this research was to study the effect of jaloh leaf extract combined with turmeric extract on the quality of broiler meat infected with Eimeria tenella (E.tenella). Sample used in this research was 20 broilers, strain Cobb aged 15 days and given treatment of jaloh extract and turmeric extract for 10 days. Meat examination was conducted after 5 days of E.tenella oocyst inoculation. There were 5 groups in this experiment (n=4), P1 as negative control was given mineral water, P2 was given commercial anti-stress 5mg/L per day, P3 was given jaloh extract 1000mg/L per day, P4 was given turmeric extract 250mg/L per day, and P5 was given jaloh leaf extract 1000mg/L combined with turmeric extract 250mg/L per day. After 25 days, all groups were infected with 1x104 concentration of E. tenella oocyst per chicken. Parameters observed in this research were organoleptic test and Postma test. The result showed that jaloh leaf extract combined with turmeric extract did not affect the quality and meat decomposition after infected with E. tenella.